Epidemiology of patient safety incidents in a long-term rehabilitative hospital in KwaZulu-Natal, South Africa (April 2011 to March 2016) - Phe Mgobozi; Ozayr H. Mahomed (AOSIS, 2021)
Background: Patient safety is a key priority of the National Department of Health. Despite the publication of legislation and other measures to address patient safety incidents (PSIs) there are a paucity of studies relating to patient safety at the different levels of hospitals. Objectives: To determine the epidemiology (incidence, nature and root causes) of PSIs at a long-term rehabilitative hospital between April 2011 and March 2016. Method: Data were collected through a review and analysis of routinely collected hospital information on patient records and from the PSI register, as well as minutes of adverse health events meetings, quality assurance reports and patient complaints register. Results: A total or 4.12 PSIs per 10 000 inpatient days were reported. Approximately 52% of the adverse health events occurred in females with most of the adverse health events occurring in the 50-59 years category: 96% being reported during the day and 33% within the shift change. Pressure ulcers, falls, injury, hospital acquired infections and medication error were the most commonly reported PSIs. Patient factors were listed as the most common root cause for the PSIs. Conclusion: The study shows a low reporting rate of PSIs whilst showing a diverse pattern of PSIs over a period of 5 years. There is a need for active change management in order to establish a blame-free culture and learning environment to improve reporting of PSI. A comprehensive quality improvement intervention addressing patients, their families and staff is essential to minimise PSI and its consequences.